(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article examines the current state and future prospects of automated design systems in engineering, focusing on the integration of optimization techniques within a systems-based design framework. The discussion includes the role of mathematical modeling, decision hierarchies, and iterative development processes in optimizing technical and economic performance. Technological advancements, particularly in CAD systems and intelligent decision-making tools, are evaluated for their contribution to modern design practices. The work also highlights challenges and opportunities in transitioning from traditional manual design methods to advanced automated approaches.